Addressing the contribution of small molecule-based biostimulants to the biofortification of maize in a water restriction scenario - Hernandiz, Alba E.; Jiménez-Arias, David; Morales-Sierra, Sarai; Borges, Andres A.; De Diego, Nuria (Frontiers in Plant Science, 2022)
Biostimulants have become an asset for agriculture since they are a greener alternative to traditionally used plant protection products. Also, they have gained the farmers' acceptance due to their effect on enhancing the plant's natural defense system against abiotic stresses. Besides commercially available complex products, small molecule-based biostimulants are very useful for industry and research. Amongst them, polyamines (PAs) are very well-studied nature compounds that can elicit numerous positive responses in drought-stressed plants. However, the studies are merely focused on the vegetative development of the plant. Therefore, we aimed to evaluate how drenching with putrescine (Put) and spermidine (Spd) modified maize production and the yield quality parameters. First, a dosage optimization was performed, and then the best PA concentrations were applied by drenching the maize plants grown under well-watered (WW) conditions or water deficit (WD). Different mechanisms of action were observed for Put and Spd regarding maize production, including when both PAs similarly improved the water balance of the plants. The application of Put enhanced the quality and quantity of the yield under WW and Spd under WD. Regarding the nutritional quality of the grains, both PAs increased the carbohydrates content, whereas the contribution to the protein content changes by the interaction between compound and growth conditions. The mineral content of the grains was also greatly affected by the water condition and the PA application, with the most relevant results observed when Spd was applied, ending with flour richer in Zn, Cu, and Ca, minerals considered very important for human health. We showed that the exogenous PA application could be a highly efficient biofortification approach. Our findings open a new exciting use to be deeper studied in biostimulant research.